Psychological Resilience of Female Students in the Psychology Department at Al-Zahraa College of Education Libya (Al-Farooq Journal of Sciences, 2026)
The current research aimed to identify the level of psychological resilience among female students in the Psychology Department at Al-Zahraa College of Education, and to reveal differences in this level according to the variable of academic year (first, second, third, fourth). The research adopted the descriptive analytical method, and the research sample consisted of (120) female students selected using stratified random sampling. To achieve the research objectives, the Psychological Resilience Scale, which was developed based on Olah's theory (Olah, 2005) and consists of (47) items in its final form, was used. The level of psychological resilience among female students in the Psychology Department was high, with a mean score of 181.59 out of 235, and a standard deviation of 7.02. Statistically significant differences in psychological resilience levels were found based on academic year, with a calculated F-value of 5.250 and a significance level of (0.002), which is less than the significance level of 0.05. These differences favored students in the upper years (fourth and third years) compared to students in the lower years (first and second years), indicating that academic experience and personal growth associated with academic progression contribute to strengthening psychological resilience. In light of these findings, the research recommends the adoption of guidance and training programs within the college to enhance the components of psychological resilience, particularly among first-year students, focusing on components such as positive thinking and self-efficacy.
Keywords: Psychological Resilience, University Students, Psychology Department, Al-Zahraa College of Education, Olah Theory